THE LIBRARIAN RELOADED: EVOLVING ROLES IN HEALTH INFORMATICS - Isip-Tan, Iris Thiele (Journal of Philippine Librarianship; Vol 37 (2017), 2019)
Discusses the potential roles of health sciences librarians in health informatics.
Keywords: heath informatics; health sciences librarians